Pediatric residents’ burnout in Indonesia: a national survey during the pandemic - Annang Giri Moelyo; Ardi Findyartini; Bambang Tridjaja; Aryono Hendarto (Indonesian Pediatric Society, 2023)
Background The uncertain and somewhat chaotic clinical learning environment during the COVID-19 pandemic may potentially trigger burnout in pediatric residents. Objective To investigate the prevalence of burnout in pediatric residents in Indonesia during the COVID-19 pandemic and to identify potential risk factors associated with burnout. Methods This analytic observational study was conducted between April and June 2020. A questionnaire-based survey using an Indonesian translation of the Maslach Burnout Inventory-Human Services Survey was conducted online across 15 pediatric training institutions treating COVID-19 patients in Indonesia. Results were interpreted in accordance with the inventory guidelines. The chi-square test was used to analyze for possible associations between each subscale and gender, marital status, training stage, as well as institution of origin. One-way ANOVA of each subscale was performed on pediatric training institutions located in different regions. Results Of 983 respondents (82% average response rate), the prevalences of high emotional exhaustion and high depersonalization were 28.0% and 15.8%, respectively, while more than half of respondents (50.2%) had a low sense of personal accomplishment. Most respondents felt more exhausted than depersonalized. The location of pediatric training institution (Java or outside Java) was the only significant factor associated with burnout (P=0.003). Conclusion In the early stages of the pandemic, more than half of pediatric residents in Indonesia had a low sense of personal accomplishment. The only significant factor associated with burnout among was the location of training institution (Java or outside Java), suggesting a potential role of differences in hospital situation and clinical learning environment during the pandemic between Java and outside Java.